2013
DOI: 10.1007/s40256-013-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Cholesterol: How Low Can We Go?

Abstract: Elevated low-density lipoprotein cholesterol (LDL-C) is an established cause of cardiovascular disease and subsequent adverse events. The efficacy and safety of lowering plasma LDL-C to reduce the risk of coronary heart disease (CHD) and secondary event rates are now well established. What has not been established, however, is a plasma LDL-C lower threshold level of safety and efficacy. Here we review intensive plasma LDL-C-lowering with statins and argue that even further reductions of plasma LDL-C than curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…There are five major lipoproteins: chylomicrons and very low-density lipoprotein, medium-density lipoprotein, low-density lipoprotein and high-density lipoprotein, which are classified compared with the density of the surrounding water [13,14]. To facilitate cell absorption and utilization of fat through receptor-mediated endocytosis, LDL carries all of the fatty molecules, cholesterol, phospholipids and triglycerides, while HDL transports cholesterol from the cells and tissues back to the liver [15]. Rather than measuring actual HDL and LDL particles, assessing HDL-C and LDL-C levels provides information about how much cholesterol is delivered by all HDL and LDL particles.…”
Section: Discussionmentioning
confidence: 99%
“…There are five major lipoproteins: chylomicrons and very low-density lipoprotein, medium-density lipoprotein, low-density lipoprotein and high-density lipoprotein, which are classified compared with the density of the surrounding water [13,14]. To facilitate cell absorption and utilization of fat through receptor-mediated endocytosis, LDL carries all of the fatty molecules, cholesterol, phospholipids and triglycerides, while HDL transports cholesterol from the cells and tissues back to the liver [15]. Rather than measuring actual HDL and LDL particles, assessing HDL-C and LDL-C levels provides information about how much cholesterol is delivered by all HDL and LDL particles.…”
Section: Discussionmentioning
confidence: 99%
“…Low-density lipoprotein cholesterol is one of the low-density lipoproteins, which can cause atherosclerosis when the content is too high [ 25 ]. And a large number of studies have shown that lowering plasma total cholesterol and low-density lipoprotein cholesterol (LDLC) can reduce the risk of cardiovascular death, myocardial infarction, and stroke [ 26 ]. In our experiment, the level of LDL-C3 was significantly decreased in the ACP group, and LDL-C3 has a tendency to decrease in the ACP+FAA group.…”
Section: Discussionmentioning
confidence: 99%
“…2 Among these risk factors, hypercholesterolemia, hypertriglyceridemia, increases in the concentrations of low density lipoproteins (LDL), and reductions in the levels of high density lipoproteins (HDL) are all important targets for attempts to prevent CVDs. 3,4 The intestinal microbiota (IM) is responsible for many different biochemical reactions and is considered an important regulator of metabolic status. 5 According to Huttenhower et al, 6 the IM is directly linked with maintenance of good health, whether intestinal or systemic.…”
Section: Introductionmentioning
confidence: 99%